Comparative Vegetation Analysis and Regeneration Status of Unlogged and Logged over Forests of South Andaman Island - Rajesh; Alappatt, Joju P. (Indian Forester, 2016)
South Andaman Island, one of the main constituents of the 'Great Andaman' group is characterized by dense tropical forests. The tropical forests of the island together with the surrounding small islands which form the South Andaman Forest Division with an area of 1665 km2 was studied for its regeneration status, composition and species diversity of commercial tree species both in the logged (worked) and unlogged (unworked) areas. It was noticed that the tree layer in unlogged forest was dominated by Dipterocarpus spp.(Gurjan) (IVI- 90.49), Knema andamanica (Jaiphal) (IVI- 48.14) and Tetrameles nudiflora (Thitpok) (IVI- 29.28) respectively in Evergreen, Semievergreen and Deciduous forests. In logged forests, Knema andamanica (IVI- 91.44), Dipterocarpus spp. (IVI- 38.94) and Pajanelia longifolia (Jhingam) (IVI- 30.73) dominated in Evergreen, Semievergreen and Deciduous forests respectively. For all the three types of forests, the co-efficient of similarity between logged and unlogged areas of each forest type was more than 50%. The composition of these species need to be maintained to manage these fragile areas so that the biodiversity rich areas are intact in its natural form.